Predictors of medical school clerkship performance: a multispecialty longitudinal analysis of standardized examination scores and clinical assessments. Issue 1 (December 2016) - Casey, Petra; Palmer, Brian; Thompson, Geoffrey; Laack, Torrey; Thomas, Matthew; Hartz, Martha; Jensen, Jani; Sandefur, Benjamin; Hammack, Julie; Swanson, Jerry; Sheeler, Robert; Grande, Joseph
Abstract Background Evidence suggests that poor performance on standardized tests before and early in medical school is associated with poor performance on standardized tests later in medical school and beyond. This study aimed to explore relationships between standardized examination scores (before and during medical school) with test and clinical performance across all core clinical clerkships. Methods We evaluated characteristics of 435 students at Mayo Medical School (MMS) who matriculated 2000–2009 and for whom undergraduate grade point average, medical college aptitude test (MCAT), medical school standardized tests (United States Medical Licensing Examination [USMLE] 1 and 2; National Board of Medical Examiners [NBME] subject examination), and faculty assessments were available. We assessed the correlation between scores and assessments and determined USMLE 1 cutoffs predictive of poor performance (≤10th percentile) on the NBME examinations. We also compared the mean faculty assessment scores of MMS students vs visiting students, and for the NBME, we determined the percentage of MMS students who scored at or below the tenth percentile of first-time national examinees. Results MCAT scores correlated robustly with USMLE 1 and 2, and USMLE 1 and 2 independently predicted NBME scores in all clerkships. USMLE 1 cutoffs corresponding to poor NBME performance ranged from 220 to 223. USMLE 1 scores were similar among MMS and visiting students. For most academic years and clerkships, NBME scores were similar for MMS students vs all first-time examinees. Conclusions MCAT, USMLE 1 and 2, and subsequent clinical performance parameters were correlated with NBME scores across all core clerkships. Even more interestingly, faculty assessments correlated with NBME scores, affirming patient care as examination preparation. USMLE 1 scores identified students at risk of poor performance on NBME subject examinations, facilitating and supporting implementation of remediation before the clinical years. MMS students were representative of medical students across the nation.